PENGARUH CAR, NPL, DAN BOPO TERHADAP ROA PADA BANK DAERAH YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lamria Sagala; Christina Silitonga; Sarmakti Situmorang; Tina Sari Tambunan (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2019)
ROA is a ratio that can demonstrate the ability of the company in generating profits using its assets. Along with the increasing of Profitability (ROA), the bank will be able to develop their businesses and face competition. The value of ROA profitability can be affected by various factors. The objective of this research is to investigate whether CAR, NPL, and BOPO have an influence on the banking company’s ROA both partially or simultaneously and to measure how much the influence. The data used in this study were obtained from the Bank’s Financial. There are three variabels that were analyzed in this study are: CAR, NPL, and BOPO.